Just like Heaven - Waters, Mark.; Heder, Jon, 1978-; Witherspoon, Reese, 1976-; Ruffalo, Mark.; Logue, Donal, 1966-; Spybey, Dina, 1966-; Shenkman, Ben.; Okada, Daryn, 1960-; Kent, Rolfe; Levy, Marc, 1961-; DreamWorks Home Entertainment (Firm); Universal Studios Home Entertainment (Firm) (Universal City, Calif. : DreamWorks Home Entertainment : Distributed by Universal Studios Home Entertainment, 2006)
Elizabeth is a dedicated, workaholic doctor who is much to busy to have a life. One night, she gets into a terrible car accident and dies. She becomes a spirit stuck between heaven and earth. She doesn't realize that she is dead and thinks nothing has happened. That is until she meets David, a lonely architect, who has rented her old apartment.
English track: Dolby digital 5.1; Dolby digital 2.0 surround.
French track: Dolby digital 5.1.
Title from container.
Based on the novel "If only it were true" by Marc Levy.
Originally released as a motion picture in 2005.
Special features: 'Making of Just like heaven'; meet the cast; deleted scenes; gag reel.
Keywords: Spirits -- Drama; Man-woman relationships -- Drama; Apartment dwellers -- Drama; Films for the hearing impaired